Effects of Topically Applied Vitamin D during Corneal Wound Healing - Reins, Rose Y. (PLoS One, 2016)
Vitamin D is an important regulator of immune function and largely acts to dampen chronic inflammatory events in a variety of tissues. There is also accumulating evidence that vitamin D acts to enhance initial inflammation, beneficial during both infection and wound healing, and then promotes resolution and prevention of chronic, damaging inflammation. The current study examines the effect of topical vitamin D in a mouse of model of corneal epithelial wound healing, where acute inflammation is necessary for efficient wound closure. At 12 and 18 hours post-wounding, vitamin D treatment significantly delayed wound closure by ~17% and increased infiltration of neutrophils into the central cornea. Basal epithelial cell division, corneal nerve density, and levels of VEGF, TGFβ, IL-1β, and TNFα were unchanged. However, vitamin D increased the production of the anti-microbial peptide CRAMP 12 hours after wounding. These data suggest a possible role for vitamin D in modulating corneal wound healing and have important implications for therapeutic use of vitamin D at the ocular surface.